2020
DOI: 10.1159/000506710
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate (Chondroitin 4) Sulfotransferase-11-Mediated Induction of Epithelial-Mesenchymal Transition and Generation of Cancer Stem Cells

Abstract: Introduction:We have previously shown that the expression of carbohydrate (chondroitin 4) sulfotransferase-11 (CHST11) is elevated in human breast cancer tissues, and that its expression in human breast cancer cell lines is associated with aggressive behavior of cells. The clinical significance of CHST11 expression is unknown, and its function in breast cancer cells is not fully understood. Objective: The current study was performed to define the clinical significance of this gene and address its biological fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Additionally, CS-A is an enzymatic substrate of CHST11, and it recruits different GFs and morphogens to guide neuron cell migration and bone and cartilage maturation in embryogenesis and bone and cartilage development, respectively [40] . Additionally, CHST11 drives breast cancer aggressiveness by inducing EMT and stem cell-like properties [41] . Besides CHST11 mRNA levels, the methylation status of this gene has potential as a prognostic biomarker in breast cancer [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CS-A is an enzymatic substrate of CHST11, and it recruits different GFs and morphogens to guide neuron cell migration and bone and cartilage maturation in embryogenesis and bone and cartilage development, respectively [40] . Additionally, CHST11 drives breast cancer aggressiveness by inducing EMT and stem cell-like properties [41] . Besides CHST11 mRNA levels, the methylation status of this gene has potential as a prognostic biomarker in breast cancer [42] .…”
Section: Discussionmentioning
confidence: 99%
“…The observations by Behrens et al [11] not only reveal the potential of CHST11 as a potential drug target, but also support the view that public databases may play an increasingly important role for reverse translational research approaches in pharmacology [12]. While such databases often do not offer direct information on the expression of biologically relevant glycans, they can provide useful information on molecules involved in glycan biosynthesis [13].…”
mentioning
confidence: 84%
“…In this issue of Pharmacology, Behrens et al [11] provide evidence for a role of carbohydrate (chondroitin 4) sulfotransferase-11 (CHST11) in the induction of epithelial-mesenchymal transition and stem cell-like properties, at least partially involving the Wnt pathway [11]. While it is known that sulfation by CHST11 alters the function of chondroitin sulfate glycosaminoglycans, the authors found that transfection of the breast cancer cell line MCF-7 with the human CHST11 gene resulted not only in the expression of chondroitin sulfate A but also in the transition from a cobblestone-like to a spindle-like shape.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the gene expression of C4ST-1 has been correlated with the progression of breast cancer ( Hazan et al, 2000 ). Most recently, Behrens et al (2020) reported a new role of C4ST-1 in the induction of epithelial–mesenchymal transition and stem cell-like properties in breast cancer. These aggressive tumor phenotypes are thought to be exerted via protein–sugar interactions that are defined by specific sulfation patterns generated by C4ST-1.…”
Section: Introductionmentioning
confidence: 99%